2002
DOI: 10.1038/sj.bjc.6600347
|View full text |Cite
|
Sign up to set email alerts
|

Immune changes in patients with advanced breast cancer undergoing chemotherapy with taxanes

Abstract: Besides cytotoxicity, taxanes induce other biological effects, especially in the immune system. Taxanes have demonstrated immunostimulatory effects against neoplasms, supporting the idea that these agents suppress cancer through several mechanisms and not solely through inhibiting cell division. The purpose of the present study was to evaluate the effect of taxanes (paclitaxel and docetaxel) and investigate their ability in alterating important immunological parameters in breast cancer patients. Thirty women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
220
4
12

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(245 citation statements)
references
References 27 publications
(32 reference statements)
9
220
4
12
Order By: Relevance
“…Patients who developed other malignancies, and patients with Creactive protein measured during a course of taxane therapy were excluded from the study since they may produce a hypersensitivity reaction and elevated concentrations of interleukin-6 (Tsavaris et al, 2002;Williams et al, 2003), which is a primary mediator of C-reactive protein (Gabay and Kushner, 1999). In total, 96 out of 295 (33%) patients with metastatic disease were eligible for the study.…”
Section: Methodsmentioning
confidence: 99%
“…Patients who developed other malignancies, and patients with Creactive protein measured during a course of taxane therapy were excluded from the study since they may produce a hypersensitivity reaction and elevated concentrations of interleukin-6 (Tsavaris et al, 2002;Williams et al, 2003), which is a primary mediator of C-reactive protein (Gabay and Kushner, 1999). In total, 96 out of 295 (33%) patients with metastatic disease were eligible for the study.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, taxol may still inhibit cytokine production and secretion by other pulmonary cell types, including epithelial and endothelial cells, resulting in a net decrease in pulmonary cytokine accumulation. Importantly, studies on breast cancer patients indicate that taxanes (paclictaxel and docetaxel) decrease levels of the serum cytokines IL-1 and TNF-a and increase levels of interferon-c, IL-2 and IL-6 [23].…”
Section: Effect Of Taxol On Lps-induced Peritonitismentioning
confidence: 99%
“…If, in fact, the major mechanism is ADCC, the combination of trastuzumab with immunosuppressive chemotherapeutic drugs requires optimal timing of trastuzumab delivery to enable rescue of ADCC effectors such as NK cells after chemotherapy. In that context, clinical studies have demonstrated a synergistic action between trastuzumab and the drug taxane (Slamon et al, 2001), which induces suppression of adaptive immunity, but selectively increases NK activity (Tsavaris et al, 2002). To improve therapeutic activity, stimulation of NK activity might also be considered, utilizing cytokines or 'danger signals' such as unmethylated CpG-oligodeoxynucleotides that enhance innate immunity (Sfondrini et al, 2002).…”
Section: Her2 As a Target For Therapymentioning
confidence: 99%